EPISTEMOLOGICAL PROOF OF COGNITIVE POSSIBILITIES OF SCIENTIST - Русяєва, Т. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the paper are considered epistemological imaginations of scientist about relation a scientific knowledge to the reality in context of science development.